Templeton Prize: for progress toward research or discoveries about spiritual realities including research in love, creativity, purpose, infinity, intelligence, thanksgiving and prayer - Unidentified author; John Templeton Foundation, publisher (Colorado State University. Libraries, 2004)
Templeton Prize brochure. Includes information on the prize; and quotes, biographies and photographs of laureates 2004, 2003, 2002 and 1999.
Dr. Rolston's quote: "Facing the new millennium, the four principal, interrelated challenges are war and peace, population, development, and environment. Science alone doesn't teach us what we most need to know about any of the four."
Keywords: winners; monetary award; laureates; Templeton Prize; religion prize